Risk Factors Associated withthe Incidence of Hypertension in Dukupuntang, Cirebon, West Java, Indonesia - Ezar Tiar Zulizar; Uswatun Khasanah; Nanang Ruhyana (Journal of Asian-african Focus in Health, 2026)
Hypertension is a major global public health problem and a leading risk factor for cardiovascular disease, stroke, and premature mortality. Despite extensive research, evidence regarding hypertension risk factors remains inconsistent across different populations and settings, particularly in rural communities. This study aimed to identify demographic, hereditary, socioeconomic, and behavioral factors associated with hypertension among adults attending the Dukupuntang Health Center, Cirebon Regency, Indonesia. A cross-sectional analytic study was conducted in June 2024 involving 147 adult respondents recruited through consecutive sampling. Data were collected using structured questionnaires, medical records, and blood pressure measurements. Hypertension was defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. Independent variables included gender, age, education level, occupation, family history of hypertension, smoking habits, physical activity, sodium intake, obesity status, and socioeconomic status. Data were analyzed using descriptive statistics and Chi-square tests with a significance level of p < 0.05. Of the 147 respondents, 51.0% were classified as hypertensive. Bivariate analysis revealed significant associations between hypertension and gender (p = 0.018), age (p = 0.015), education level (p = 0.015), occupation (p = 0.010), and family history of hypertension (p < 0.001). In contrast, smoking habits (p = 0.056), physical activity (p = 0.154), sodium intake (p = 0.808), obesity status (p = 0.134), and socioeconomic status (p = 0.301) were not significantly associated with hypertension. Hypertension in this rural population was primarily associated with demographic, hereditary, and social determinants. These findings highlight the importance of targeted screening, health education, and family-history-based prevention strategies to strengthen hypertension control and cardiovascular disease prevention in rural communities.